Forwarding/Routing with Dual Names: The NovaGenesis Approach - Alberti, Antonio M.; Santos, Jose R. dos; Morais, Everton S. de; Santos, Rodrigo H.; Magalhães, Vaner J. (Anais do Workshop de Pesquisa Experimental da Internet do Futuro (WPEIF), 2018)
Name-based forwarding/routing (NBFR) is an emerging approach to provide location-independent delivery in Future Internet (FI). It provides identifier-based communication independently of location. Even tough many FI proposals support NBRF for specific ingredients (e.g. contents or hosts), therefore a generic approach is missing. Also, current proposals, like CCN, XIA and NetInf do not employ self-verifying names (SVNes) alternatively as identifiers and/or locators (making dual use of SVNes, saving storage resources). Another novelty is to employ the same BNFR structure not only horizontally (among nodes), but also inside nodes vertically (among operating systems, processes and its components). This paper provides a proof-of-concept of NovaGenesis Forwarding/Routing with Dual Names (FRDN). FRDN enables unlimited name-based data plane with SVNes. Future work includes performance evaluation in a large experimental setup, for instance employing Brazilian FIBRE research network in the context of future Internet interconnection point (FIXP) project.